1994
DOI: 10.1111/j.1432-1033.1994.tb18758.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence on proline‐specific enzymes of a substrate containing the thioxoaminoacyl–prolyl peptide bond

Abstract: Dipeptidyl peptidase IV from porcine kidney and aminopeptidase P from Escherichia coli can utilize thioxoalanyl-proline 4-nitroanilide but with decreased kinetic constants compared to the normal substrates. Product analysis showed that exclusively thioxoalanyl-proline was liberated in the case of dipeptidyl peptidase IV catalysis and thioxo-alanine in the case of aminopeptidase-P-mediated thioxo peptide bond hydrolysis. For the proline-specific aminopeptidase P the k,,/K,,, value for the thioxo peptide is 1100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…Moreover, the chemical reactivity of thioxo peptide bonds is as high as their 0x0 peptide counterparts 127-291. In contrast, carboxypeptidase A [7,8,101 and aminopeptidase P [14] can hydrolyse a thioxylated amide bond, but with a decrease in k,,, of about 1 000-fold. Furthermore, the thioxo peptide N-(furylacry1oyl)-Phe-r//[CS-NH]-Gly-Pro represents a fairly good substrate for the metalloprotease angiotensin-converting enzyme [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the chemical reactivity of thioxo peptide bonds is as high as their 0x0 peptide counterparts 127-291. In contrast, carboxypeptidase A [7,8,101 and aminopeptidase P [14] can hydrolyse a thioxylated amide bond, but with a decrease in k,,, of about 1 000-fold. Furthermore, the thioxo peptide N-(furylacry1oyl)-Phe-r//[CS-NH]-Gly-Pro represents a fairly good substrate for the metalloprotease angiotensin-converting enzyme [27].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, scissile peptide bond thioxylation usually enhances stability toward hydrolysis by various proteolytic enzymes . Studies on papain [15], dipeptidylpeptidase IV [14], and prolyl oligopeptidase [131 that involved proteolytic cleavage of substrates thioxylated at nonscissile peptide bonds, have also indicated a reduction in the magnitude of the specificity rate constant.…”
mentioning
confidence: 99%
“…This was demonstrated for carboxypeptidase A,15,17 prolyl endopeptidase,18 aminopeptidase P and dipeptidyl peptidase IV. 19 Recently it was shown that thioxo peptides act as competitive inhibitors for the peptidyl-prolyl cis/trans isomerase cyclophilin A21 known as the cytosolic receptor for the immunosuppressive undecapeptide cyclosporin A.…”
Section: Introductionmentioning
confidence: 99%
“…A downÐeld shift is observed for both the CSwNH protons (1.5È2 ppm) and the CS carbons (30 ppm). 19 The position of a thioxo peptide bond can be assigned by multidimensional NMR experiments along with complete assignment of the entire set of 1H and 13C signals.12 However, NMR is a time-and material-intensive method. Additionally, the analysis of polypeptides may be very difficult and the investigation of polypeptide mixtures cannot be performed at all.…”
Section: Introductionmentioning
confidence: 99%
“…Endothio analogues of biologically active peptides can show protease resistance, thus allowing higher bioavailability [14]. In addition, enhanced biological activity [15] and receptor selectivity [16] can be expected.…”
mentioning
confidence: 99%